Study of the potential of Caregiver for the Elderly after 70 hours of Elderly Care Program Of Boromarajonani College of Nursing, Surat Thani - แซ่ติ๋ว, ปภาสินี; จินต์คณาพันธ์, ชไมพร; เรืองสวัสดิ์, ศราวุธ; ทีปะปาล, ธนิดา (Journal of The Royal Thai Army Nurses, 2019)
The objective of the Mixed Methods Research was to study the results of the potential development of the elderly caregivers and the opinions of the related persons about the potential of elderly caregivers after completing one year of training. Sample group is Village public health volunteers who passed 107 elderly care curricula, 10 elderly care users. The research instrument was a potential questionnaire for elderly caregivers and interviewing elderly caregivers. Using statistics, percentage, mean and standard deviation. The research reveals that the samples were knowledgeable about chronic diseases and care for the elderly after being trained at a high level. 83.1%. 10.2% were at a moderate level, and 6.5% were at low level. the elderly caregivers had overall skills in elderly care management and the level of satisfaction was high level ( = 3.98, S.D. = 0.88) The high motivation in managing elderly care was overall high ( = 4.09, S.D. = 0.87) The self-concept in caring for the elderly was overall at a high level ( = 3.88, S.D. = 0.80) The good quality in caring the elderly was at a high level ( = 4.36, SD = 0.63). Based on interviews with related people, it was found that Caregivers have more knowledge, know their roles and duties. The caregivers can correctly evaluate the elderly ’s symptoms by using what they have been trained. They also having caring skills in for the bed-ridden elderly, and the caring caused the elderly ‘s improvement can be the motivation and pride that makes the caregivers of the elderly have the intention to continue working.